2000
DOI: 10.1093/hmg/9.6.987
|View full text |Cite
|
Sign up to set email alerts
|

The proteolipid protein gene and myelin disorders in man and animal models

Abstract: The two proteins, proteolipid protein and DM20, which are encoded by alternative transcripts from the proteolipid protein ( PLP ) gene, are major components of central nervous system myelin. In man, mutations of these proteins cause Pelizaeus-Merzbacher disease (PMD), an X-linked dysmyelinating neuropathy. The mutations found are very varied, ranging from deletions, loss-of-function and missense mutations to additional copies of the gene. This same range of known genetic defects has been observed in animal mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 51 publications
0
36
0
2
Order By: Relevance
“…MBP is also a myelin component and mutations in Mbp are responsible for the shiverer mouse phenotype which involves deficient CNS myelination as well as tremors and convulsions, a phenotype that is reversed by introduction of a functional Mbp gene (Readhead et al, 1987). Plp1 is genetically associated with Pelizaeus–Merzbacher disease, a hypomyelinative leukodystrophy (Yool et al, 2000), and deletion of Plp1 from the mouse leads to axonal disruption suggesting that olidodendrocytes are required for axon function (Edgar et al, 2004b). Mice deficient in Ugt8a show hypomyelination as well as increased numbers of oligodendrocytes (Marcus et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…MBP is also a myelin component and mutations in Mbp are responsible for the shiverer mouse phenotype which involves deficient CNS myelination as well as tremors and convulsions, a phenotype that is reversed by introduction of a functional Mbp gene (Readhead et al, 1987). Plp1 is genetically associated with Pelizaeus–Merzbacher disease, a hypomyelinative leukodystrophy (Yool et al, 2000), and deletion of Plp1 from the mouse leads to axonal disruption suggesting that olidodendrocytes are required for axon function (Edgar et al, 2004b). Mice deficient in Ugt8a show hypomyelination as well as increased numbers of oligodendrocytes (Marcus et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who suffer from Pelizaeus-Merzbacher disease (PMD), in addition to rodent models of PMD, carry mutations in the PLP gene. This gene encodes the proteolipid protein (PLP) and its shorter isoform DM20, the two most abundant membrane proteins in myelin [106]. The consequences of disease-related PLP gene duplication, which are phenotypically more severe than null mutations, include the accumulation of PLP in mitochondria.…”
Section: Genetically Inherited Mitochondrial Syndromesmentioning
confidence: 99%
“…Other transgenic studies have demonstrated that overexpression of the Plp gene leads to glial cell degeneration and hypomyelination [133,134] or late-onset neurodegeneration [135]. This sensitivity to moderate overexpression of the Plp gene may help to explain why humans who have Plp gene duplications develop PMD [reviewed in 136].…”
Section: Temporal Regulation Of Plp Gene Expressionmentioning
confidence: 99%